STRATEGIC MANAGEMENT OF PROPERTIES (International Journal of Innovative Technologies in Economy, 2021)
This paper is dedicated to the study of strategic management techniques for improving the return on in-vestment of a real estate company with techniques of increasing the financial leverage and reduction of sys-temic risk and specific risk of this kinds of companies. Some strategies are proposed with different capital allocation hypothesis and related result are provided.